FRACTURE NETWORK ANALYSIS OF META-SEDIMENTARY ROCK IN EAST COAST TERENGGANU; AN ANALOGUE TO FRACTURED BASEMENT IN MALAY BASIN - Ooi , Phey Chee (Universiti Teknologi PETRONAS, 2015)
Oil and gas exploration have now moved to the basement rocks. Basement are rocks with low matrix porosity and permeability, therefore fractures provide a path for hydrocarbon flow and storage. The research aims to establish an outcrop that could possibly be an analogue to the fractured basement of the Malay Basin and to apply seismic attributes to enhance the image of seismic data obtained from a chosen field in the Malay Basin, thereby reducing the uncertainty of interpretation. Kuala Abang outcrop in Terengganu has been chosen to be an example of exposed basement in the Malay Basin. The metasediments in Kuala Abang are 21m wide and 8m tall, with beds dipping at 340°/60°. Fracture measurements were recorded and analyzed using the rose diagram. Results shows the Shear1Left is positioned at 340° whereas the Shear1Right is orientated at 270°. Therefore the mazimum stress σ 1 is located at NNW-SSE while the minimum stress σ 3 at ENE-WSW. 3D seismic data of Puteri Field in the Malay Basin was utilized for fracture characterization of the reservoir basement. Seismic interpretation was first done, followed by the interpretation of fractures using seismic attributes as image enhancer. The attributes used are structural smoothing, variance and curvature attributes. Seismic interpretation shows one major fault and four seismic units whereby the lithology is generally sandstone and siltstone in a fluvial environment. The basement are not metasediment due to a presence of feldspar. Fractures are beyond the resolution of seismic data, therefore the approach to this problem is by analyzing the azimuth of the major fault. The stress orientation of the fault is relatable to the stress direction of fractures, as both are within the same stress field. The fault analysis results in a NNW-SSE maximum stress direction. Although it is correlatable to the stress measurements of Kuala Abang, the difficulties faced are the difference in lithology, age and scale of the outcrop and Puteri Field. Nonetheless, the seismic attributes are excellent methods to assist in the study of fractured basement.